(untitled) (Global Journal of Medical Research, 2018)
Mycobacterium is acid fast genus of bacteria that include many pathogenic and non pathogenic species. Tuberculosis (TB) is the leading cause of death in the world from a bacterial infectious disease. The emergence of antibiotic resistance strains has raised the need towards the development of new antibiotics or drug molecules which can kill or suppress the growth of pathogenic Mycobacterium species. The increasing emergence of drug-resistant tuberculosis along with the HIV pandemic (human) threatens disease control and highlights both the need to understand how our current drugs work and the need to develop new and more effective drugs. Novel efforts in developing drugs that target the intracellular metabolism of M. tuberculosis often focus on metabolic pathways that are specific to mycobacterium. Potential drug targets were also identified from pathways related to lipid metabolism, carbohydrate metabolism, amino acid metabolism, energy metabolism, vitamin and cofactor biosynthetic pathways and nucleotide metabolism. Approximately one-fourth of the Mycobacterium tuberculosis genome contains genes that encode proteins directly involved in its metabolism. This review provides a brief historical account of tuberculosis drugs, metabolic pathways, examines the problem of current chemotherapy, discusses the targets of current tuberculosis drugs with focuses on some metabolic pathways. The identification of drug target form that unique metabolism of mycobacterium is crutial to to develop new drug for persistent and latent infection of tuberculosis.